2022
DOI: 10.1007/s00259-022-05676-1
|View full text |Cite|
|
Sign up to set email alerts
|

CEST MRI provides amide/amine surrogate biomarkers for treatment-naïve glioma sub-typing

Abstract: Purpose Accurate glioma classification affects patient management and is challenging on non- or low-enhancing gliomas. This study investigated the clinical value of different chemical exchange saturation transfer (CEST) metrics for glioma classification and assessed the diagnostic effect of the presence of abundant fluid in glioma subpopulations. Methods Forty-five treatment-naïve glioma patients with known isocitrate dehydrogenase (IDH) mutation and 1p/19… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 48 publications
(58 reference statements)
0
15
0
Order By: Relevance
“…Careful interpretation is needed with post‐operative‐stage tumors with the surgical cavity filled with proteinaceous fluid, unless a fluid suppression method is used (Figure 10C and D). 56,111 To distinguish between viable tumor and proteinaceous fluid, APTw images should generally be interpreted together with anatomic MRI (such as T 2 w, fluid‐attenuated inversion recovery (FLAIR), and pre‐ and post‐contrast T 1 w), SWI, diffusion, and perfusion (including dynamic susceptibility contrast‐enhanced and dynamic contrast‐enhanced) MRI sequences that are acquired during routine clinical tumor protocols. This comparison helps, on one hand, to recognize and assign non‐tumorous signals and potential artifacts on APTw images and, on the other hand, to identify tumor viability characteristics, which are not captured by the structural and perfusion‐weighted MRI (Figure 10D).…”
Section: Data Interpretationmentioning
confidence: 99%
See 2 more Smart Citations
“…Careful interpretation is needed with post‐operative‐stage tumors with the surgical cavity filled with proteinaceous fluid, unless a fluid suppression method is used (Figure 10C and D). 56,111 To distinguish between viable tumor and proteinaceous fluid, APTw images should generally be interpreted together with anatomic MRI (such as T 2 w, fluid‐attenuated inversion recovery (FLAIR), and pre‐ and post‐contrast T 1 w), SWI, diffusion, and perfusion (including dynamic susceptibility contrast‐enhanced and dynamic contrast‐enhanced) MRI sequences that are acquired during routine clinical tumor protocols. This comparison helps, on one hand, to recognize and assign non‐tumorous signals and potential artifacts on APTw images and, on the other hand, to identify tumor viability characteristics, which are not captured by the structural and perfusion‐weighted MRI (Figure 10D).…”
Section: Data Interpretationmentioning
confidence: 99%
“…Key abbreviations and nomenclatures used in the field of APTw imaging are listed in Table 1. Data from numerous institutions worldwide have demonstrated that APTw imaging adds important value to the standard clinical MRI sequences in brain cancer diagnoses, such as the detection and grading of tumors, 22–37 the assessment of treatment effect versus tumor recurrence, 38–45 prognosis related to tumor progression and survival, 46–48 and the identification of genetic markers 49–56 . It is worth mentioning that brain tumor patients require frequent MRI exams, and the exposure to gadolinium (Gd)‐based contrast agents has been indicated as a risk for people with moderate to advanced kidney failure and for Gd deposition in the brain 57–59 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…39 To remove the artifacts caused by areas of large cysts and liquefied necrosis, a possible solution (fluid suppression) has been proposed to suppress the APTW signal of large cyst or liquefaction necrosis. 40,41 However, this APTW metric needs to be validated further. Compared with 3D-APTW imaging, the diagnostic performance of 3D-PcASL imaging showed a moderate diagnostic performance in differentiating TP from TR, and the rCBF values of the TP group were significantly higher than those of the TR group (p < 0.001), which is consistent with previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…When evaluating TP or TR of glioma, APTW images should be combined with anatomic MRIs (such as T2WI, pre‐and post‐contrast T1WI, and FLAIR) to distinguish tumor recurrence from large cysts and liquefied necrosis with proteinaceous fluid 39 . To remove the artifacts caused by areas of large cysts and liquefied necrosis, a possible solution (fluid suppression) has been proposed to suppress the APTW signal of large cyst or liquefaction necrosis 40,41 . However, this APTW metric needs to be validated further.…”
Section: Discussionmentioning
confidence: 99%